MaABI5 and MaABF1 transcription factors regulate the expression of MaJOINTLESS during fruit abscission in mulberry (Morus alba L.) - Deng, Xuan; Ahmad, Bilal; Deng, Jing; Liu, Lianlian; Lu, Xiuping; Fan, Zelin; Zha, Xingfu; Pan, Yu (Frontiers in Plant Science, 2023)
Mulberry holds significant economic value. However, during the ripening stage of its fruit, the phenomenon of abscission, resulting in heavy fruit drop, can severely impact the yield. The formation of off-zone structures is a critical factor in the fruit abscission process, and this process is regulated by multiple transcription factors.One such key gene that plays a significant role in the development of the off-zone in the model plant tomato is JOINTLESS, which promotes the expression of abscissionrelated genes and regulates the differentiation of abscission zone tissue cells. However, there is a lack of information about fruit abscission mechanism in mulberry. Here, we analyzed the MaJOINTLESS promoter and identified the upstream regulators MaABF1 and MaABI5. These two regulators showed binding with MaJOINTLESS promoter MaABF1 (the ABA Binding Factor/ABA-Responsive Element Binding Proteins) activates activated the expression of MaJOINTLESS, while MaABI5 (ABSCISIC ACID-INSENSITIVE 5) inhibited the expression of MaJOINTLESS. Finally, the differentially expressed genes (DEGs) were analyzed by transcriptome sequencing to investigate the expression and synergistic relationship of endogenous genes in mulberry during abscission. GO classification and KEGG pathway enrichment analysis showed that most of the DEGs differentially expressed genes were concentrated in MAPK signaling pathway, flavonoid biosynthesis, citric acid cycle, phytohormone signaling, amino acid biosynthesis, and glycolysis. These results provide a theoretical basis for subsequent in-depth study of physiological fruit abscission in mulberry.